Impact of the Flipped Classroom on Knowledge Retention Among Undergraduate Students at the Higher Institute of Nursing Professions and Health Techniques in Fez - Lamsyah Rajae; Essadki Samia; Archou Rachida; Wahoud Fatima; Hajjaji Wissam; Azzaoui Mohammed; Zahouani Chadia; Elmsellem Hicham; El Bouazzaoui Abderrahim; Kanjaa Nabil (E3S Web of Conferences)
The Flipped Classroom (FC) approach is increasingly recognized for enhancing student engagement and knowledge retention. This study evaluates its impact on undergraduate nursing students at the Higher Institute of Nursing Professions and Health Techniques in Fez, Morocco. A quasi-experimental design was used, comparing two groups: one following the FC model and the other a traditional lecture-based approach. A total of 120 students were randomly assigned to either the FC (n=60) or the Traditional Classroom (TC) (n=60) group. Knowledge retention was assessed through module. The FC group demonstrated significantly higher academic performance, with a mean score of 17.39 ± 1.11 compared to 14.11 ± 3.03 in the TC group (U = 3098.0, p< 0.0001). Moreover, all FC students validated the module, compared to 90% in the TC group (χ2 = 4.39, p = 0.036). These findings suggest that the FC model fosters deeper engagement and better knowledge retention, making it a promising pedagogical alternative, particularly in nursing education where critical thinking is essential. However, further research is needed to assess its long-term effects across diverse educational settings.